2018
DOI: 10.1177/0333102418811573
|View full text |Cite
|
Sign up to set email alerts
|

Acute migraine therapy with external trigeminal neurostimulation (ACME): A randomized controlled trial

Abstract: ObjectiveTo assess the safety and efficacy of external trigeminal nerve stimulation for acute pain relief during migraine attacks with or without aura via a sham-controlled trial.MethodsThis was a double-blind, randomized, sham-controlled study conducted across three headache centers in the United States. Adult patients who were experiencing an acute migraine attack with or without aura were recruited on site and randomly assigned 1:1 to receive either verum or sham external trigeminal nerve stimulation treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 29 publications
4
110
1
4
Order By: Relevance
“…In fact, the study on nVNS for acute treatment of migraine did not meet its primary endpoint of pain free at 2 hours post‐treatment (therapeutic gain of 10.7%), which was successfully achieved in the current study, with a therapeutic gain of 19.0%. The therapeutic gain of pain free at 2 hours in the current study was also higher than the therapeutic gain of 10% reported for external trigeminal nerve stimulation . To compare the efficacy of REN to that of triptans, we analyzed the pain relief and pain‐free responses at 2 hours post‐treatment in attacks with moderate or severe baseline pain intensity.…”
Section: Discussionmentioning
confidence: 62%
“…In fact, the study on nVNS for acute treatment of migraine did not meet its primary endpoint of pain free at 2 hours post‐treatment (therapeutic gain of 10.7%), which was successfully achieved in the current study, with a therapeutic gain of 19.0%. The therapeutic gain of pain free at 2 hours in the current study was also higher than the therapeutic gain of 10% reported for external trigeminal nerve stimulation . To compare the efficacy of REN to that of triptans, we analyzed the pain relief and pain‐free responses at 2 hours post‐treatment in attacks with moderate or severe baseline pain intensity.…”
Section: Discussionmentioning
confidence: 62%
“…There has been a single randomized, sham‐controlled, double‐blind study looking at the use of STNS for the acute treatment of migraine . This study, called the ACME trial (acute migraine therapy with external trigeminal neurostimulation) recruited 106 patients from 3 medical centers, all of whom had migraine, and randomized them 1:1 to receive either true or sham stimulation at migraine onset.…”
Section: Neuromodulation For Treatment Of Migrainementioning
confidence: 99%
“…There has been a single randomized, sham-controlled, double-blind study looking at the use of STNS for the acute treatment of migraine. 6 This study, called the ACME trial (acute migraine therapy with external trigeminal neurostimulation) recruited 106 patients from 3 medical centers, all of whom had migraine, and randomized them 1:1 to receive either true or sham stimulation at migraine onset. Subjects were told to treat their attack with their assigned device for 1 hour, and the primary outcome was the mean change in pain intensity (using the 1-10 visual analog scale) at 1 hour compared to baseline.…”
Section: Neuromodulation For Treatment Of Migrainementioning
confidence: 99%
“…2 In addition to causing significant pain, migraine causes children and adolescents to miss school, negatively affects school performance, leads to high health care costs for affected families, and has profound economic impact. [6][7][8][9][10][11][12][13] Pediatric studies are now getting underway to meet regulatory requirements. 4,5 Recently developed novel therapeutics, including drugs, biologics, and neuromodulation devices, are safe and welltolerated in adults.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Recently developed novel therapeutics, including drugs, biologics, and neuromodulation devices, are safe and welltolerated in adults. [6][7][8][9][10][11][12][13] Pediatric studies are now getting underway to meet regulatory requirements. Both the US Food and Drug Administration (FDA) and the European Medicines Agency require pediatric studies in order to assess safety, pharmacokinetics, and efficacy in children.…”
Section: Introductionmentioning
confidence: 99%